PF-429242, a Subtilisin Inhibitor, Is Effective in vitro Against Leishmania infantum - Machado, Patrícia de Almeida; Gomes, Pollyanna Stephanie; Midlej, Victor; Coimbra, Elaine Soares; de Matos Guedes, Herbert Leonel (Frontiers in Microbiology, 2021)
PF-429242 is an inhibitor of subtilisin, an important protease found in Leishmania. However, studies regarding the effect of PF-429242 on Leishmania are scarce. In this work we evaluated the antileishmanial effect of PF-429242 against Leishmania infantum and the mechanism involved in the death of the parasite. PF-429242 had low toxicity against mammalian cells (peritoneal macrophages) (CC50 = 189.07 µM) and presented good activity against L. infantum promastigotes (IC50 = 2.78 µM) and intracellular amastigotes (IC50 = 14.07 µM), indicating selectivity towards the parasite. Transmission electron microscopy (TEM), as well as staining of L. infantum promastigotes with MitoTracker® Red, rhodamine 123 and MitoSOX, revealed that the mitochondria was a potential target of PF-429242. In addition, PF-429242 caused an accumulation of neutral lipids in promastigotes, which was demonstrated by Nile Red staining and TEM, and induced oxidative stress (H2DCFDA staining). Furthermore the formation of autophagic vacuoles in L. infantum promastigotes was observed by MDC staining and TEM. However, the killing induced by PF-429242 in L. infantum promastigotes appeared to be unrelated to apoptosis and/or necrosis as there was no phosphatidylserine externalization, DNA fragmentation or alterations in the permeability of the parasite plasma membrane, as assessed by annexin V-FITC, TUNEL and propidium iodide staining, respectively. The morphological and ultrastructural evaluation of the promastigotes by optical microscopy, scanning electron microscopy (SEM) and TEM, revealed the presence of parasites with flagellar defects. TEM analysis of the intracellular amastigotes indicated that mitochondrial damage and autophagy could also be involved in the death of these forms after treatment with PF-429242. In addition, PF-429242 treatment stimulated NO production from infected macrophage, but only at a high concentration (100 µM), as well as an increase of TNF levels after treatment with 10 µM of PF-429242. The compound did not stimulate ROS or IL-10 production. Together, these data highlight the antileishmanial potential of PF-429242, inducing several cellular alterations in the parasite, such as mitochondrial damage, neutral lipids accumulation, oxidative stress and autophagy which culminate in the death of L. infantum, as well as modulating host cellular responses that favor the development of an immune response against the parasite.